Interspecies Loop Grafting in the Protease Domain of Human Protein C Yielding Enhanced Catalytic and Anticoagulant Activity - Shen, Lei; Villoutreix, Bruno O.; Dahlbäck, Bjorn (Thrombosis and Haemostasis, 1999)
Human anticoagulant activated protein C (hAPC) is less potent than the bovine APC (bAPC) molecule and our aims were to elucidate the molecular background for this difference and to create an APC with enhanced anticoagulant activity. In the protease domain of human protein C (hPC), the loop 148 (GWGYHSSREKEAKRN) is four residues longer than the corresponding loop in bovine APC (GWGY RDETKRN). To investigate whether this caused the species difference, the loop in hPC was replaced by the shorter bovine loop, whereas the longer human loop was introduced in bovine protein C. The mutation in hAPC yielded enhanced catalytic activity against chromogenic (4-fold) as well as natural (factors Va and VIIIa) substrates and 2-3-fold increased anticoagulant activity. The opposite effects were obtained with the bovine mutant. As compared to wild-type hAPC, the mutant hAPC was inhibited slightly faster by the protein C inhibitor, whereas the inhibition by α 1-antitrypsin was unaffected by the mutation. A computer model of bAPC was developed in order to analyse further our data. Collectively, our results demonstrate enhanced catalytic efficiency to result from mutagenesis in the loop 148 and show that APC mutant with increased anticoagulant activity can be created.Abbreviations: PC, protein C; APC, Activated protein C. SDS-PAGE, polyacrylamide gel electrophoresis run in the presence of SDS, The chymotrypsinogen nomenclature for APC and thrombin is used throughout the text while the PC numbering is indicated between brackets whenever appropriate. P2, P1 and P1’, P2’.. designate inhibitor residues amino- and carboxy-terminal to the scissile peptide bond, respectively, and S2, S1 and S1’, S2’.. the corresponding subsites of the protease. APTT, activated partial thromboplastin time; rmsd, root mean square deviation. The coordinates of the bAPC model are freely available.